Tren Pencatatan Laporan Cakupan Kunjungan K4 Puskesmas di Dinas Kesehatan Kota Surabaya Tahun 2015–2017 - Siti Rohmatun Ni'mah; Soenarnatalina Melaniani (Universitas Airlangga, 2019)
One of the management of health information systems are reported and processed like data regarding coverage of K4 pregnant women. The coverage visited of pregnant women Surabaya in 2017 is 98.55% of 47,104 pregnant women. That indicator has been used assess maternal and child health services. This can be identified by the completed coverage of antenatal care (supply service standards and keeping the time set), which describes the ability of management or continuity of the maternal and child health program. The study was carried out to describe the trend of the coverage report system K4 pregnant woman visits at the Surabaya City Health Office in 2015–2017. This research is a descriptive study with a quantitative approachment, the data used by secondary data from the Surabaya City Health Profile Report from 2015 to 2017. The data were based on coverage of K4 pregnant women from 2015 to 2017, there are several publiic health centers with report trends visits to K4 pregnant women which tend to declined and less than the target of 98.45% that have been fixed in the Strategic Plan of Surabaya City Health Office. Three health center whose trend of data has decreased from 2014–2017 are Tembok Dukuh Health Center, Simokerto Health Center, and Menur Health Center. This is due to an error in the reporting mechanism both in data input, data processing, and output, it is necessary to develop an infoormation system for recording and reporting on maternal health services, especially for pregnant women and evaluating reports on K4 pregnant women's visits.